Colloidally prepared Pt nanowires versus impregnated Pt nanoparticles comparison of adsorption and reaction properties - Haghofer, Andreas (Langmuir : the ACS journal of surfaces and colloids, 2010)
Ligand-capped Pt nanowires, prepared by colloidal synthesis and deposited on a high surface area γ-Al(2)O(3) support, were subjected to surface characterization by electron microscopy and FTIR spectroscopy using CO as a probe molecule. The structural, adsorption, and catalytic reaction properties of the colloidal Pt nanowires were compared to those of conventional, impregnated Pt nanoparticles on the same Al(2)O(3) support. In situ FTIR spectroscopy indicated ligand effects on the CO resonance frequency, irreversible CO-induced surface roughening upon CO adsorption, and a higher resistance of colloidal catalysts toward oxidation (both in oxygen and during CO oxidation), suggesting that the organic ligands might protect the Pt surface. Elevated temperature induced a transformation of Pt nanowires to faceted Pt nanoparticles. The colloidal catalyst was active for hydrodechlorination of trichloroethylene (TCE), but no ligand effect on selectivity was obtained